Improving reporting of observational studies of interventions: The TARGET guideline - Hansford, Harrison J.; McAuley, James H.; Cashin, Aidan G. (PLoS medicine, 2025)
Emulating a target trial when conducting an observational study of interventions can reduce the likelihood of design-related biases. The TARGET guideline aims to improve the reporting transparency of observational studies emulating a target trial and help readers appraise and apply the results.